2021
DOI: 10.1177/20551029211065614
|View full text |Cite
|
Sign up to set email alerts
|

The role of parent-to-child maltreatment in the pathway of self-reported depressive symptoms in Pakistani adolescents

Abstract: Background Parent-to-child maltreatment has been demonstrated to drastically affect a child’s mental well-being and plays a significant role in developing depressive symptoms. However, little is established about the effect of frequency of parent-to-child maltreatment on the development of depressive symptoms among Pakistani adolescents. Methods A longitudinal prospective study was conducted, from 2015 to 2017, with 800 adolescents aged 11–17 years old recruited from 32 systematically selected urban and peri-u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Moreover, a study disclosed that childhood experiences of neglect and maltreatment serve as the source of self-criticism in adulthood (Bruefach et al, 2021). Also, the findings of Lakhdir et al (2021) suggested that frequent parent-to-child maltreatment occurring during childhood leads to the development of depressive symptoms later in adolescence.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a study disclosed that childhood experiences of neglect and maltreatment serve as the source of self-criticism in adulthood (Bruefach et al, 2021). Also, the findings of Lakhdir et al (2021) suggested that frequent parent-to-child maltreatment occurring during childhood leads to the development of depressive symptoms later in adolescence.…”
Section: Introductionmentioning
confidence: 99%